The crime of mafia-association and the Palermo Convention (Rivista di Studi e Ricerche sulla criminalità organizzata, 2020)
In order to combat organized crime - including the mafia type - which is acquiring an increasingly global and transnational dimension, it is absolutely necessary to develop equally global and transactional repressive and preventive responses. The Palermo Convention moves in this direction thanks to the identification of a minimum common denominator in the definition of "organized criminal group", acceptable, and accepted, in the legislation of many States.
Keywords: Organized Crime, Mafia-Association, Palermo Convention, Organized Criminal Group, Transnational Crime